Determinants of Handwashing Without Soap in Tanzania: Evidence from the 2015/16 Tanzania Demographic Health Malaria Indicator Survey (Tanzania Journal for Population studies and Development, 2022)
Handwashing with soap can reduce pathogens, leading to a reduction in the spread of diarrhoea and other diseases. Handwashing with soap is insufficiently practised in Tanzania despite its potential health benefits. This study identifies the determinants of high levels of handwashing without soap in rural and urban areas of Tanzania. It used the 2015/16 Tanzania Demographic Health Survey - Malaria Indicator Survey (TDHS-MIS) dataset. A sample of 9,695 households—3,058 from urban areas and 6,637 households from rural areas—were used in the analysis. Pearson chi-square test and multivariate logistics regression analysis were used to determine the association between the independent and dependent variables. The study found that handwashing without soap was more prevalent in rural areas (46%) than in urban areas (28%). Exposure to the media (listening to the radio in rural areas and watching television in urban areas), and improved access to water sources decreased the probability of handwashing without soap, both in rural and urban areas. A household-headed by a female, and a household-head who was married, showed a decreased odd of handwashing with water only in rural areas; while households with 7 and more members showed increased odds of handwashing with water only in rural areas. The study concludes that exposure to the media and improved access to water sources can reduce high rates of handwashing without soap in Tanzania. Efforts to reduce handwashing without soap should target urban and rural communities since handwashing is a complex human behaviour.